WORKSHOP PENGEMBANGAN MODUL AJAR DEEP LEARNING BAGI GURU SEKOLAH DASAR - Feny Rita Fiantika; Danang Prastyo; Dian Kusmaharti (Universitas PGRI Adi Buana Surabaya, 2026)
This activity is a Community Service activity carried out by the Community Service Team of Elementary School Teacher Education lecturers, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya. The purpose of this service activity is to improve teacher competence in developing Deep Learning teaching modules. Participants in this activity are teachers who are members of MGMP throughout Ketidur Mojokerto sub-district and this activity was carried out at SDN Ketidur Mojokerto on November 24, 2025 using presentation, modeling, and simulation methods accompanied by assignments. The results of the workshop showed that participants were able to understand and design Deep Learning teaching modules well, participants were motivated in participating in the Deep Learning teaching module workshop, and there were changes in knowledge/competence in developing Deep Learning teaching modules.